Can PSMA-Targeting Radiopharmaceuticals Be Useful for Detecting Hepatocellular Carcinoma Using Positron Emission Tomography? An Updated Systematic Review and Meta-Analysis - Alessio Rizzo; Manuela Racca; Domenico Albano; Francesco Dondi; Francesco Bertagna; Salvatore Annunziata; Giorgio Treglia (Pharmaceuticals, 2022)
Background: Several studies proposed the use of positron emission tomography (PET) with Prostate-Specific Membrane Antigen (PSMA)-targeting radiopharmaceuticals in hepatocellular carcinoma (HCC). Our aim is to calculate the detection rate (DR) of this examination in HCC with a meta-analysis. Methods: A comprehensive literature search of studies on the DR of PET/CT or PET/MRI with PSMA-targeting radiopharmaceuticals in HCC was performed. Original articles evaluating these imaging examinations both in newly diagnosed HCC patients and HCC patients with disease relapse were included. Pooled DR including 95% confidence intervals (95% CI) was calculated. Statistical heterogeneity was also assessed using the I2 test. Results: The meta-analysis of six selected studies (126 patients) provided a DR of 85.9% for PET imaging with PSMA-targeting radiopharmaceuticals in the diagnosis of HCC. Moderate statistical heterogeneity among the included studies was found (I2 = 56%). Conclusions: The quantitative data provided demonstrate the high DR of PET/CT or PET/MRI with PSMA-targeting radiopharmaceuticals for HCC lesion detection. However, more studies are needed to confirm the promising role of PSMA-targeted PET in HCC.